2020
DOI: 10.1080/2162402x.2020.1738812
|View full text |Cite
|
Sign up to set email alerts
|

An innovative plasmacytoid dendritic cell line-based cancer vaccine primes and expands antitumor T-cells in melanoma patients in a first-in-human trial

Abstract: The efficacy of immune checkpoint inhibitors has been shown to depend on preexisting antitumor immunity; thus, their combination with cancer vaccines is an attractive therapeutic approach. Plasmacytoid dendritic cells (PDC) are strong inducers of antitumor responses and represent promising vaccine candidates. We developed a cancer vaccine approach based on an allogeneic PDC line that functioned as a very potent antigen-presenting cell in pre-clinical studies. In this phase Ib clinical trial, nine patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 40 publications
0
73
0
1
Order By: Relevance
“…Once activated via TLR7/9L, pDCs potentially achieve tumor control through efficient priming of antitumor responses 47,48 . Tumor antigen‐loaded pDCs properly activated can be vectors for immunotherapy and elicit favorable antitumor immune responses in patients upon vaccination 49,50 . Besides, the role of cDC1s in antitumor immunity, mostly described in mouse models, is poorly known in humans 51‐53 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once activated via TLR7/9L, pDCs potentially achieve tumor control through efficient priming of antitumor responses 47,48 . Tumor antigen‐loaded pDCs properly activated can be vectors for immunotherapy and elicit favorable antitumor immune responses in patients upon vaccination 49,50 . Besides, the role of cDC1s in antitumor immunity, mostly described in mouse models, is poorly known in humans 51‐53 .…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Tumor antigen-loaded pDCs properly activated can be vectors for immunotherapy and elicit favorable antitumor immune responses in patients upon vaccination. 49,50 Besides, the role of cDC1s in antitumor immunity, mostly described in mouse models, is poorly known in humans. [51][52][53] cDC1s are present in peripheral tissues where they capture tumor antigens and, after migration to tumordraining lymph nodes, activate antitumor CD4 + and CD8 + T cells.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed several human plasmacytoid dendritic cell (PDC) lines from leukemic cells of a patient having a PDC leukaemia for research and development (R&D) applications [ 8 , 9 ] or for clinical applications [ 10 ]. One of them, the clinical-grade cell line named ‘PDC*line’ is grown in cell suspension in a synthetic medium without the need for any feeder cell, growth or maturation factor.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that PDC*line cells were more potent than moDC to activate and expand potent antitumor T-cells [ 13 ]. With this PDC*line, we have developed a new cell-based vaccine approach named GeniusVac/PDC*vac that was first used to boost antitumor immunity in HLA-A*02:01 melanoma patients with a cell therapy product named GeniusVac-Mel4 [ 10 ]. The cell product was composed of the irradiated PDC*line cells loaded with four tumour HLA-A*02:01-restricted peptides derived from antigens expressed in melanoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation